PENGUJIAN FILTER PARTIKULAT ASAP ROKOK ELECTROSTATIC PRECIPITATOR DENGAN ELEKTRODA TEMBAGA DAN ALUMUNIUM - Anggraini, Ika Novia (JURNAL AMPLIFIER : JURNAL ILMIAH BIDANG TEKNIK ELEKTRO DAN KOMPUTER, 2023)
Cigarette smoke is a source of air pollution, especially indoors. The smoke from burning cigarettes doesn't just evaporate into the air, but there is nicotine residue that sticks to the dust or items around the smoker, such as clothes, carpets, walls. A smoke filter or smoke particulate filter is something that is really needed to reduce pollutants in the room. Research on "Testing Electrostatic Precipitator (ESP) Cigarette Smoke Particulate Filters with Copper and Aluminum Electrodes" aims to analyze the comparison of the use of copper and aluminum electrodes as filters on ESP. In this research, a high voltage DC generator was used using the full-wave cascade method, for the high voltage that was successfully generated by this full-wave cascade method was 2.25 kV to 5.46 kV. From the test results, it was found that the difference in (∆ levels between the inlet and outlet containers (∆ using a copper plate was higher than using an aluminum plate. In addition, it can be concluded that increasing the voltage causes more (∆ levels to be filtered.